India and global economic governance: from structural conflict to embedded liberalism - Mukherji, Rahul (International studies review, 2014)
India's behavior in the global economy has transformed considerably, consistent with its embrace of economic globalization and deregulation since 1991. Until then, India had practiced a type of economic engagement that Stephen Krasner (1985) characterized as structural conflict. Its capacity to tax citizens was dismal. Its trade as proportion of gross domestic product (GDP) hovered around 16% in the 1980s, impeding growth. And, economic resources were redistributed authoritatively rather than through trade. India, like many developing countries, was locked in economic conflict with the West until the 1980s. Since then, it has embraced global economic integration, contributing to surging economic growth. An economy that grew at an average of 3.5% between 1956 and 1975 has grown at more than 6% since 1980 and over 7% since 2004. India is one of the fastest growing economies in the world after China, and the gap...
Gesehen am 11.12.2017